Managing knowledge workers value assessment, methods, and application tools - Patalas-Maliszewska, Justyna (Management for professionals, 2013)
This book focuses on understanding the strategic role of the knowledge workers in  companies, especially in creating an innovative company. The author presents the 'Sknowinnov method' and a decision-making model for the assessment of the value of strategic knowledge resources in companies. This method and its approach can be used as excellent tools for a quantitative knowledge analysis in an economic viewpoint. The IT tool that is developed for this method offers support in decision making at a strategic level regarding the profitability of any investment in employee qualifications and skills. The tool also connects the selected determinants described in an innovative company with the value of the personnel usefulness function, enabling the assessment of the rationality and effectiveness of knowledge. HR managers and knowledge management consultants for innovative companies would find this book and the IT tools presented specially useful. This book also adds value to researchers dealing with analysis of quantitative and qualitative methods in intellectual capital research.